2013
DOI: 10.1002/app.39485
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of emulsion‐type curing agent of water‐borne epoxy resin

Abstract: Self-emulsified water-borne epoxy curing agent of nonionic type was prepared using triethylene tetramine (TETA) and derivative of epoxy resin as a capping agent, which was synthesized by liquid epoxy resin (E51) and polyethylene glycol (PEG), and the curing agent possessed emulsification and curing properties at the same time. The curing agent with good property of emulsifying liquid epoxy resin could be obtained under the condition of the molar ratio of PEG : E51 : TETA as 0.8 : 1 : 3.5 at 80 C for 5 h. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
(12 reference statements)
1
13
0
Order By: Relevance
“…Moreover, the mean particle size of the emulsion tends to increase. Similar results were also reported by Sun et al . in the case of preparing an emulsion‐type curing agent.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, the mean particle size of the emulsion tends to increase. Similar results were also reported by Sun et al . in the case of preparing an emulsion‐type curing agent.…”
Section: Resultssupporting
confidence: 90%
“…However, small molecular amine curing agent easily absorbs moisture and carbon dioxide in the air, which results in bleaching, adhesion falling, high brittleness of the cured film. Recently, more attention has been paid to the modified amine epoxy curing agent to overcome the above defects . A waterborne curing agent based on liquid epoxy resin and polyamine was prepared by Waler, but the performance of cured film was not satisfactory due to the poor intermiscibility between the curing agent and epoxy resin.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the FTIR spectra of epoxy resin, ET3, ET6, and ET9 coatings. The absorption peak located at 913 cm −1 could be assigned to the stretching vibration of the saturated epoxy ring; the one at 1409 cm −1 represents O-H bending vibrations in epoxy resin [ 6 , 10 ]. In the spectrum of the coating without the agent, both peaks could be observed clearly, which meant the cross-linking degree of resin was at a low level.…”
Section: Resultsmentioning
confidence: 99%
“…They found that hardness, water resistance, and adhesion of the cured film were improved significantly [ 9 ]. Sun et al synthesized a self-emulsified waterborne epoxy cross-linking agent of nonionic type using triethylene tetramine (TETA), and they found that epoxy resin film cured by the agent under ambient conditions showed good properties even at high staying temperature [ 10 ]. Although films cross-linked through ring-open mode usually showed good water resistance and corrosion resistance within a short period, the durability of the performance needs to be improved urgently.…”
Section: Introductionmentioning
confidence: 99%
“…Component B is a curing agent for epoxy resins, which helps bind epoxy molecules together. Currently, there are many methods of curing epoxy resin by chemical [9,10,11], and UV light [12]. Chemical curing agents such as polyamide, aromatic diamine with hetero-cyclic side chain structure, amido amide, cyclo aliphatic [13].…”
Section: Introductionmentioning
confidence: 99%